Calculation of Integral Indicators of the Metabolic Status and Filtration Function of Kidneys in Patients with a Combat Mine-Explosive Injury who Lost Significant Body Weight due to Limb Amputation - Sydorova, Nataliia; Kazmirchuk, Kateryna; Kolisnyk, Oleh; Tsaralunha, Vira; Kobirnichenko, Yuliia; Sydorova, Liudmyla (Acta medica Lituanica, 2025)
Background: The aim of this retrospective cohort study was to investigate the possibility of optimizing the calculation of integral indicators of the metabolic status and filtration function of the kidneys in patients with combat mine-explosive injuries who have lost significant body weight due to limb amputation. Methods: Data from 81 servicemen (all males) with combat mine-explosive limb injuries, including those with isolated severe limb injuries (Group 1, n=34) or traumatic amputations (Group 2, n=47), were analyzed. We assessed demographic indicators and the glomerular filtration rate (GFR), calculated according to the generally accepted formulas with correction for lost body parts in the amputees. Results: The proportion of amputees with obesity as measured by the body mass index in Group 2 without correction for the lost body parts was significantly lower than that in Group 1 and Group 2 adjusted for the lost body parts (2.12% versus 17.65% and 21.28%, respectively, p<0.05 and p<0.01), but it was similar in Group 1 and Group 2 after body weight adjustment for the lost body parts of the amputees (p>0.05). The mean level of serum creatinine in the patients in Group 2 was significantly lower than that in Group 1 (75.19±11.62 vs. 90.93±37.12 μmol/L, respectively, p=0.0206). The estimated GFR according to the Cockcroft and Gault formula (CGF) with adjusted for the lost body part body weight was significantly greater in Group 2 than that in Group 1 (143.63±42.58 and 123.92±26.34 mL/min/1.73m2, respectively, p=0.0379) as well as GRF according to CGF corrected for the body surface area (BSA) (131.59±39.94 and 106.17±21.88 mL/min/1.73m2, respectively, p=0.0040). Only a few individuals had a moderate decrease in GFR according to CGF or CGF adjusted for BSA, but glomerular hyperfiltration was suspected in a significant number of patients, specifically, 23.53% and 17.65% of the patients in Group 1, respectively, and in 29.79% and 36.17% of the patients in Group 2, respectively (even 51.6% according to CGF corrected for BSA in Group 2 adjusted for the lost body parts). Conclusions: In amputees, it is necessary to calculate their body weight considering the lost body part for an adequate assessment of their metabolic status. To calculate GFR, it is advisable to use CGF considering the lost body parts with or without adjustment for BSA to avoid the possibility of underestimating GFR calculated by other formulas. Special control is necessary for patients with hyperfiltration suspected by CGF, since this sign can be a predictor of future metabolic disorders.